2022
DOI: 10.1155/2022/6274670
|View full text |Cite
|
Sign up to set email alerts
|

Enterprise Operational Resilience with Digitalization Approach amid the COVID‐19 Era: An Empirical Assessment

Abstract: The development of the COVID-19 pandemic has had a devastating impact on one Chinese city that has depended heavily on tourism, which is the core focus of the current study. This article uses phenomenological research methods in qualitative research to conduct semistructured and in-depth interviews with travel agency managers in China Highlights. Through the application of tourism resilience theory in the tourism crisis management domain, this article investigates the performance of China Highlights, a local t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…However, from the perspective of enterprise internal revolution, there is still little research on improving corporate resilience through digitalization. A few works of literature only discuss the positive impact of enterprise digitalization [ 12 , 13 ]. In addition, existing literature only discusses the influence mechanism of digitalization on firm resilience from the perspectives of enterprise digital innovation [ 14 ], human capital [ 15 ], and business networks [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, from the perspective of enterprise internal revolution, there is still little research on improving corporate resilience through digitalization. A few works of literature only discuss the positive impact of enterprise digitalization [ 12 , 13 ]. In addition, existing literature only discusses the influence mechanism of digitalization on firm resilience from the perspectives of enterprise digital innovation [ 14 ], human capital [ 15 ], and business networks [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Netography is a research methodology that aims to provide a more comprehensive understanding of travel experiences and is frequently integrated into tourism branding strategies [ 70 , 71 ]. This approach considers services as the supportive process that ultimately creates value for tourists.…”
Section: Methodsmentioning
confidence: 99%
“…Through questionnaire analysis, Jiao found that customer participation would have a positive impact on employees' performance, thereby improving enterprise performance [52]. For tourism enterprises, resilience is crucial for facilitating accurate forecasting after the COVID-19 pandemic [53]. Moreover, studies have indicated that social interactions can alleviate travel fatigue caused by COVID-19 [54].…”
Section: Tourists' Participationmentioning
confidence: 99%